1991
DOI: 10.2337/diab.40.11.1382
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Molecules in Human Islet β-cells: De Novo Induction of ICAM-1 but Not LFA-3

Abstract: Understanding how T lymphocytes recognize beta-cell autoantigens is essential for the elucidation of the pathogenesis of insulin-dependent diabetes mellitus. The increased and ectopic expression of HLA class I and II molecules detected in human beta-cells may facilitate this interaction. T-lymphocyte recognition of surface antigens also involves adhesion accessory molecules: intercellular adhesion molecule 1 (ICAM-1) and lymphocyte function-associated antigen 3 (LFA-3). These molecules not only allow cell cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…It has been shown that TNF-a can induce the expression of ICAM-1 on human islet B cells (20,21 ). This was confirmed on rat cells in the course of the present study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It has been shown that TNF-a can induce the expression of ICAM-1 on human islet B cells (20,21 ). This was confirmed on rat cells in the course of the present study.…”
Section: Discussionsupporting
confidence: 76%
“…Furthermore, the cytokine TNF-a has been shown to induce the expression of a CAM, the intercellular CAM-l (ICAM-1), on pancreatic endocrine B cells (20,21 ). Thus, in addition to allowing the attachment of cytotoxic lymphocytes, this cytokine might initiate islet dysfunction by the induction of unusual CAMs, with the resulting loss of islet cell type segregation, or by modifying the expression of constitutive CAMs responsible for normal cell type adhesion and segregation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental studies (36,37) demonstrated that pancreatic islet cells could express adhesion molecules, as well as MHC molecules, when stimulated by IFN-,y and/or TNF-a in vitro, suggesting the possible participation of the molecules in the pathogenesis of IDDM. Therefore, we analyzed two adhesion molecules, ICAM-1 and LFA-3, in IDDM pancreases.…”
Section: Discussionmentioning
confidence: 99%
“…The results of TAP-1 flow cytometry were clearly reproducible (CV < 10%). To assess better the distribution of TAP-1 in the cytoplasm of thyrocytes, monolayer cultures were also stained as described [19].…”
Section: Methodsmentioning
confidence: 99%